Western European integration and Eastern European transformation - Karl Hans Hartwig; Paul J. J. Welfens (Intereconomics, 1996)
The process of EU integration has intensified in the 1980s and early 1990s. The desire of a number of central and eastern European countries to join the EU is often seen as a threat to the continuation of this process. How wide should the radius of EU enlargement be? Which forms of integration would be appropriate between the EU and different subsets of ex-CMEA countries?
Keywords: 330; EU Enlargement